TREE-BASED MIXED EFFECTS MODELING OF TEACHER CERTIFICATION OUTCOMES IN MADRASAH ALIYAH: A COMPARATIVE STUDY OF GLMM TREES AND GMET - Dodi Irawan Syarip; Khairil Anwar Notodiputro; Bagus Sartono (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
The Teacher Professional Education program, or “Pendidikan Profesi Guru” (PPG), is a continuing education program designed for prospective or in-service teachers to obtain a teaching certificate. PPG is a priority program of the Ministry of Religious Affairs in providing competent and professional madrasah teachers. This study is expected to identify the challenges encountered in the implementation of the Madrasah teacher certification program and provide valuable input to enhance the success rate of Madrasah Aliyah teachers in the PPG program. The main objective of this study is to find the most appropriate tree-based mixed effects model to analyze the effectiveness of PPG for Madrasah Aliyah teachers in 2022. This study applies two tree-based mixed effects modeling methods: generalized linear mixed model trees (GLMM trees) and generalized mixed effects trees (GMET). Both methods model variability across subjects as a random effect. Based on the performance indices measurement results, the GMET model shows superiority over the GLMM trees model. The GMET model has an accuracy index of 0.7653, higher than the GLMM trees model of 0.7306. Substantively, teachers of English and Indonesian Language exhibit higher probabilities of passing than those of other subjects, whereas Arabic and Islamic Cultural History have the lowest estimated probabilities of success. Analysis of the variable importance from both models indicates that teachers’ age is the most influential predictor of PPG graduation among Madrasah Aliyah teachers. Based on these findings, to improve the effectiveness of PPG implementation for madrasah Aliyah teachers, policymakers at the Ministry of Religious Affairs are advised to implement a structured coaching and mentoring program for prospective PPG participants, with a special emphasis on support for senior teachers specializing in Arabic and Islamic Cultural History.